Biochemical genetics - Emmanuel Shapira (Oxford University Press, 1989)
The most comprehensive laboratory manual of its kind, this book summarizes the common assays and laboratory procedures used for the diagnosis of genetic biochemical disorders. Written in cookbook fashion, it provides detailed descriptions of the procedures currently used in the diagnostic work-up of patients with underlying inherited inborn errors of metabolism. General procedures and buffer preparations are discussed. Fluorometric and spectrophotometric assays for lysosomal and non-lysosomal enzymes, radioisotope methods, and tests for metabolic disorders such as qualitative spot tests and thin-layer chromatography are included. For each assay, the authors list the tissues to which it has been applied, control ranges for leukocyte and fibroblast preparations, and commercial sources of substrates. Clear and concise, this guidebook is designed to be accessible even to those with limited experience, and will be an invaluable aid for genetics laboratories and medical geneticists